World War II, the Baby Boom, and Employment: County-Level Evidence - Brodeur, Abel; Kattan, Lamis (Journal of Labor Economics, 2022)
This paper examines the impact of male casualties due to World War II on fertility and female employment in the United States. We rely on the number of casualties at the county level and use a difference-in-differences strategy. While most counties in the United States experienced a baby boom following the war, we find that the increase in fertility was lower in high-casualty-rate counties than in low-casualty-rate counties. Analyzing the channels through which male casualties could have decreased fertility, we provide evidence that county male casualties are positively related to 1950s female employment and household income.